2014
DOI: 10.1175/jcli-d-13-00121.1
|View full text |Cite
|
Sign up to set email alerts
|

Summer Rainfall Variability in Low-Latitude Highlands of China and Subtropical Indian Ocean Dipole

Abstract: Based on reanalysis and observational datasets, this study proposes a reasonable mechanism for summer rainfall variations over the low-latitude highlands (LLH) of China, in which a subtropical Indian Ocean dipole (SIOD)-like pattern is the key external thermal forcing. In summers with a positive SIOD-like pattern, sea surface temperature (SST) anomalies may lead to lower-tropospheric divergence over the tropical Indian Ocean and convergence over the subtropical southwestern Indian Ocean and Arabian Sea. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…One branch of the corresponding upper-level outflows converges over the Indo-China peninsula, which is favorable for anomalous descending motion and lower-level northeasterly anomalies, both of which favor decreased rainfall in SWC. This is consistent with the results revealed by Cao et al [2], who showed that the summer rainfall in SWC is negatively connected with the subtropical Indian Ocean dipole on interannual timescale. The positive subtropical Indian Ocean dipole facilitated easterly anomalies off the eastern coast of BOB and weakened climatological water vapor flux to the northern BOB.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…One branch of the corresponding upper-level outflows converges over the Indo-China peninsula, which is favorable for anomalous descending motion and lower-level northeasterly anomalies, both of which favor decreased rainfall in SWC. This is consistent with the results revealed by Cao et al [2], who showed that the summer rainfall in SWC is negatively connected with the subtropical Indian Ocean dipole on interannual timescale. The positive subtropical Indian Ocean dipole facilitated easterly anomalies off the eastern coast of BOB and weakened climatological water vapor flux to the northern BOB.…”
Section: Discussionsupporting
confidence: 93%
“…The climatological summer rainfall in SWC gradually decreases from southeast to northwest, with values ranging between 5 mm day −1 and 8 mm day −1 (Figure 1). Unlike flatlands, agriculture and ecosystems in this region are quite vulnerable to summer rainfall variability in low-latitude highlands [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While SST variability in other ocean basins has also been connected to IAV in China (e.g. Qiu et al, 2014;Cao et al, 2014), Stephan et al (2017a) did not find an influence of other basins on their EOT patterns. Therefore, we here focus on the teleconnection to ENSO.…”
Section: Teleconnection To Ensomentioning
confidence: 85%